(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study investigated reward management strategy as predictors of teachers’ work attitude and mental well-being in secondary schools in Nsukka Education Zone. The study was guided with two research questions and two corresponding hypotheses that were tested at 0.05 level of significance. The design was a correlation survey with a population of 450 teachers with poor work attitude and mental well-being challenges in the 32 public secondary schools in Nsukka Education Zone of Enugu State, Nigeria. The sample size of 100 teachers was drawn using Taro Yamanene formula. Three self-designed measures titled Reward Management Strategy Scale (RMSS) Teachers’ Work Attitude Scale (TWAS) and Teachers Mental Well-Being Scale (TMWBS) were used for data collection. The scales were face validated by experts and the internal consistency reliability coefficients of 0.78, 0.88 and 0.81 were computed for RMSS, TWAS and TMWBS through the use of Cronbach alpha. Simple regression was used to answer the research questions while t-test associated with simple regression was used to test the null hypotheses at 0.05 level of significance. The result of this study revealed that principals’ reward management strategy significantly predicts 72.9% of teachers work attitude and 94.0% of teachers’ mental well-being. Based on the conclusion and findings of this study, the researcher recommended that the principals should provide the needed and basic reward management such as recognition, compensation, capacity building programmes, housing and health insurance schemes in order to promote teachers work attitude and mental well-being in secondary schools in Nsukka Education Zone of Enugu State.